(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2019)
The Shari’a law has determined that al-Mafqud (a missing person) is not considered to be dead but requires evidence or investigation for a certain period of time. After the evidence shows that the missing person has died then al-Mafqud is considered to be deceased. This study was conducted employing a qualitative methodology and the data was obtained through library research and analysed descriptively. The results of the study show that al-Mafqud should not be regarded as a haqiqi (actual) or hukmi (presumptive) death because a person who al-Mafqud is considered to be alive until decided otherwise by a judge. The study found that no substantive laws have been legislated for al-Mafqud cases in the country, there are no uniform laws in the administration of al-Mafqud’s estate. The study concludes that al-Mafqud is entitled to inherit the estate of his deceased benefactor based on faraid law in the Syariah. Keywords: Islamic law, faraid, inheritance, al-Mafqud